Diagnostic concordance of different criteria for exercise pulmonary hypertension in subjects with normal resting pulmonary artery pressure. Issue 1 (30th March 2016) - Godinas, Laurent; Lau, Edmund M.; Chemla, Denis; Lador, Frédéric; Savale, Laurent; Montani, David; Jaïs, Xavier; Sitbon, Olivier; Simonneau, Gérald; Humbert, Marc; Hervé, Philippe
Pulmonary hypertension is defined by a resting mean pulmonary artery pressure (mPAP) ≥25 mmHg [1]. Despite a better understanding of the biology of pulmonary hypertension and new therapeutic advances, pulmonary hypertension remains diagnosed late in its natural history and is largely a non-curable condition [2]. Recently, there has been renewed interest in stress-testing of the pulmonary circulation since the early stages of pulmonary vascular disease (PVD) or left heart disease (LHD) can be associated with normal resting mPAP but an abnormal haemodynamic response that is unmasked by exercise [3–5]. Methodology of pressure–flow assessment needs to be standardized for the diagnosis of exercise pulmonary hypertension http://ow.ly/YMgZw